Pathophysiology of bradykinin and histamine mediated angioedema - Lima, Hermenio; Zheng, Jiayue; Wong, Dennis; Waserman, Susan; Sussman, Gordon L. (Frontiers in Allergy, 2023)
Angioedema is characterized by swelling localized to the subcutaneous and submucosal tissues. This review provides an overview of angioedema, including the different types, triggers, and underlying pathophysiologic mechanisms. Hereditary and acquired angioedema are caused by dysregulation of the complement and kinin pathways. In contrast, drug-induced and allergic angioedema involve the activation of the immune system and release of vasoactive mediators. Recent advances in the understanding of the pathophysiology of angioedema have led to the development of targeted therapies, such as monoclonal antibodies, bradykinin receptor antagonists, and complement inhibitors, which promise to improve clinical outcomes in patients with this challenging condition. To accurately diagnose and manage angioedema, an understanding of this condition's complex and varied pathophysiology is both necessary and critical.